Autism and schizophrenia spectrum disorder: phenomenological qualitative study of patients’ experience - Jeličić, Aleksandra; Drobnič Radobuljac, Maja; Sass, Louis; Škodlar, Borut (Frontiers in Psychiatry, 2025)
ObjectiveAutism spectrum disorder (ASD) and schizophrenia spectrum disorder (SSD) overlap in behavioral signs, particularly in social functioning; consequently, SSD patients are frequently misdiagnosed with ASD and vice versa. The neurodevelopmental and spectrum nature of both disorders, including milder variants, further complicates differential diagnosis, which calls for a better differentiation by looking at the subjective experience of patients. To our knowledge, no prior clinical studies have directly and comparatively examined the subjective experiences of individuals from these two spectra. The present study adopts a phenomenological approach traditionally applied to SSD; it reveals qualitative similarities and differences in these two spectra: in the experience of oneself, the world, and interpersonal relationships.MethodsThe study included 42 participants, aged 15 to 26, all with at least average intelligence and no acute psychiatric symptoms, as verified by the Symptom Checklist (SCL-90-R). We interviewed participants in depth on their experiences and applied the Examination of Anomalous Self-Experience (EASE), and selected parts of the Examination of Anomalous World-Experience (EAWE).ResultsDifferences were observed across all five EASE domains, with higher levels in the SSD as compared to ASD in minimal self-disorder, demarcation phenomena, paranoid anxiety, short term memory disorder, and magical thinking. Meanwhile, obsessive thinking, attention problems, diminished presence in the world, social anxiety, and hyper-reflectivity overlapped in both groups. The most significant qualitative overlapping within EAWE were in abnormalities within social interactions, increased auditory perception intensity and synesthesia. Within overlaps important qualitative differences are noted and described.ConclusionsDespite considerable overlap in outer manifestations, we found important qualitative differences that point to the centrality of a disorder of ipseity in the SSD versus of primary intersubjectivity in ASD.